Foreign investment, transnationals and developing countries - Lall, Sanjaya; Streeten, Paul. (London : Macmillan, 1977)
This book examines the impact of the transnational corporation (TNC) on the economy of developing countries. Its main concern is the formulation of policies by a host country designed to promote the country's developmental objectives and at the same time to extract the maximum possible economic rents from the foreign enterprise.
Includes index.
Includes bibliographical references: p. 251-272.
lje 17/01/2018
Loans
Keywords: Investments, Foreign; International business enterprises; Developing countries